Phenolic Compound Content in Different Organs of Korean Common Buckwheat Cultivars - Romij Uddin, Md; Li, Xiaohua; Tae Park, Woo; Bok Kim, Yeon; Ju Kim, Sun; Seon Kim, Young; Young Lee, Mi; Ho Park, Cheol; Un Park, Sang (Asian Journal of Chemistry, 2012)
In this study the variation in phenolic compounds among cultivars of common buckwheat from Korea was evaluated. On analyzing the different parts of this plant, nine different phenolic compounds-rutin, epicatechin, chlorogenic acid, 4-hydroxy benzoic acid, catechin, 4-hydroxy-3-methoxy benzoic acid, p-coumaric acid, quercetin and kaempferol were identified. The levels of these phenolic compounds varied not only significantly among the cultivars but also between plant organs. The amount of phenolic compounds in the flower was much higher than that in the leaf, stem and root of the plant, while the levels of phenolic compounds in any given plant part varied widely among the cultivars. None of the cultivars had the highest amount of any particular phenolic compounds in all the parts of the plant. The Suwon 1 cultivar was found to contain the highest levels of catechin and epicatechin, while the greatest amount of 4-hydroxy benzoic acid, chlorogenic acid, 4-hydroxy-3-methoxy benzoic acid and rutin were present in Suwon 2. Thus, the Suwon 2 cultivar dominated over other cultivars, with the highest phenolic compound content in the stem, flower and roots of common buckwheat.